Book Review: The Vaccinators: Smallpox, Medical Knowledge, and the 'Opening' of Japan - Thompson, C Michele (EASTM: East Asian Science, Technology and Medicine, 2013)
Keywords: book.review; dept.his

Tuệ Tĩnh Vietnamese Monk-Physician at the Ming Court - Thompson, C Michele (The Illustrated History of Chinese Medicine and Healing, 2013)
Keywords: dept.his

Sabbatical leave report: Fall 2013 - Nakamura, Byron (Distribution: Fall 2013 ; History., 2013)
This leave was devoted to research and revision of two conference papers submitted for publication, and to revision of a book chapter on boxing in the antiquity The chapter was submitted and accepted for publication in the Cambridge Companion to Boxing series.
Keywords: dept.his; faculty_collection; sabbatical_report

Divergent paths: Processes of identity formation among German speakers, 1730-1760 - McDaniel, M.B. (A Peculiar Mixture: German-Language Cultures and Identities in Eighteenth-Century North America, 2013)
Journal Abbreviation: A Peculiar Mixture: German-Language Cultures and Identities in Eighteenth-Century N. Am.
Keywords: dept.his

Friday Night Fighter: Gaspar "Indio" Ortega and the Golden Age of Television Boxing - Rondinone, Troy (University of Illinois Press, 2013)
Friday Night Fighter relives a lost moment in American postwar history, when boxing ruled as one of the nation's most widely televised sports. During the 1950s and 1960s, viewers tuned in weekly, sometimes even daily, to watch widely-recognized fighters engage in primordial battle, with the Gillette Cavalcade of Sports Friday Night Fights being the most popular fight show. Troy Rondinone follows the dual narratives of the Friday Night Fights show and the individual story of Gaspar "Indio" Ortega, a boxer who appeared on primetime network television more than almost any other boxer in history. From humble beginnings growing up poor in Tijuana, Mexico, Ortega personified the phenomenon of postwar boxing at its greatest, appearing before audiences of millions to battle the biggest names of the time, such as Carmen Basilio, Tony DeMarco, Chico Vejar, Benny "Kid" Paret, Emile Griffith, Kid Gavilan, Florentino Fernández, and Luis Manuel Rodriguez.–(Source of description unspecified.)
Keywords: Hispanic Americans; History; History; Boxing; History; Television broadcasting of sports; Ortega; Gaspar "Indio"; 1935-; Boxing; United States; United States; Sports; dept.his; faculty_collection

“No Man’s Land”: Forbidden and Subversive Space in War - Paddock, Troy R. E. (Environment, Space, Place, 2013)
0 citations (Crossref) [2023-10-31]
Keywords: dept.his

"Grating the Nutmeg: Slavery, Race and Sectionalism in Connecticut from the Colonial Era to the Civil War" - Forbes, Robert Pierce (Connecticut History, 2013)
Keywords: dept.his; ⛔ No DOI found

Book Review: A nation of deadbeats: an uncommon history of america's financial disasters - Rondinone, Troy (The Journal of American History, 2013)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/101-519-269-502-947 tex.type: [object Object]
Keywords: book.review; dept.his

The caliph and the heretic: ibn sabaʾ and the origins of shī’ism, by sean w. anthony - Judd, Steven C. (Information Systems, 2013)
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00410 tex.type: [object Object]
Keywords: dept.his